ANALISIS DAYA SAING DAN FAKTOR YANG MEMENGARUHI NILAI EKSPOR KOMODITAS TIMAH INDONESIA DI PASAR INTERNASIONAL - Sani, Andin Meilenia; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022, 2022)
This study aims to analyze the competitiveness of Indonesian tin export commodities in the international market, the direct effect of exchange rates and international prices on the value of Indonesian tin exports, the direct effect of exchange rates, international prices, and export values ??on the competitiveness of Indonesian tin, and to determine the relationship between exchange rates and international prices indirectly affect the competitiveness of Indonesian tin. This research was conducted in the range of 1990-2019. The research data were analyzed using path testing with the help of SPSS (Statistical Product and Service Solutions) 26 for windows. The results show that (1) Indonesian tin has a very high comparative advantage where the RCA index is > 1 in the period 1990-2019. (2) The Exchange Rate does not directly affect the Export Value of Indonesian Tin. (3) International prices have a positive and significant effect on the Value of Indonesian Tin Exports. (4) Exchange Rate has a positive and significant impact on the competitiveness of Indonesian Tin. (5) International prices have a negative and significant effect on Indonesia's Tin Competitiveness. (6) Exchange Rate does not have an indirect effect on the Competitiveness of Indonesian Tin, while International Prices have an indirect influence on the Competitiveness of Indonesian Tin.